2022
DOI: 10.3390/diagnostics12020330
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Atresia: A Complex Hepatobiliary Disease with Variable Gene Involvement, Diagnostic Procedures, and Prognosis

Abstract: The diagnosis of biliary atresia is still terrifying at the 3rd decade of the 21st century. In a department of neonatal intensive care unit, parents and physicians face a challenge with a jaundiced baby, who may or may not have a surgically correctable hepatopathy. The approach has been systematically evaluated, but the etiology remains ambiguous. The study of families with recurrent biliary atresia has been undertaken at a molecular level. The primary interest with this disease is to identify the etiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Notably, one of the most connected proteins is adducin 3 (ADD3), involved in the assembly of the actin filament network at sites of cell-cell contact. This gene is a marker of biliary atresia 53 , a pathology also associated to HCMV infection 54 . Functions related to adhesion and extracellular matrix organization are also over-represented in the rest of the communities, consistent with a global downregulation of these processes in HCMV infected cells 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, one of the most connected proteins is adducin 3 (ADD3), involved in the assembly of the actin filament network at sites of cell-cell contact. This gene is a marker of biliary atresia 53 , a pathology also associated to HCMV infection 54 . Functions related to adhesion and extracellular matrix organization are also over-represented in the rest of the communities, consistent with a global downregulation of these processes in HCMV infected cells 55 .…”
Section: Resultsmentioning
confidence: 99%
“…The underlying reason for the discrepancy may be due to differences in population genetics and predisposition to environmental factors between the East and West. Several candidate genes, such as ADD3 and GPC1, have been shown to associate with BA 144 . A viral trigger causing biliary obstruction in utero has long been considered a possible aetiological factor.…”
Section: Hepatobiliarymentioning
confidence: 99%
“…The influence of antenatal exposure to environment factors such as cytomegalovirus (CMV), intraamniotic infection, and medication therapy on BA pathogenic mechanisms is uncertain [ 10 ]. Accumulating evidence demonstrated that genetic element might be of key importance for the pathogenesis of BA [ 11 ]. Genome-wide association studies (GWASs) have found that certain genes, such as ADD3 and XPNPEP1 , may increase a person's susceptible to BA [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%